Association between Backfat Depth and Litter Size at Birth in Primiparous Sows - Atthaporn Roongsitthichai,; Seri Koonjaenak,; Padet Tummaruk, (Agriculture and Natural Resources, 2011)
This study was undertaken to investigate the association between backfat thickness (BF) at insemination and litter size at the birth of first parity sows. In total, 201 Landrace × Yorkshire crossbred gilts raised in a conventional open housing system from the eastern region of Thailand were included. The measurement of BF was performed using A-mode ultrasonography at the first mating day, the 70th day of gestation period, and 1 wk prior to farrowing. The gilts were categorized on the criterion of BF at the mating day into three groups: high (17–20 mm), moderate (14–16.5 mm), and low (11.0–13.5 mm). The results revealed that the gilts in the high group possessed the biggest litter size (13.1 ± 0.5 piglets), compared to the moderate and the low groups which had 12.0 ± 0.4 and 12.0 ± 0.6 piglets per litter, respectively.